1970
DOI: 10.4314/ejhs.v28i6.4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Trends of Major Transfusion Transmissible Infections among Blood Donors in Dire Dawa Blood bank, Eastern Ethiopia: Retrospective Study

Abstract: BACKGROUND: Acquisition of transfusion transmissible infections in the process of therapeutic blood transfusion is a major global health challenge in transfusion medicine. This study aimed to determine the prevalence and trends of major transfusion transmissible infections among blood donors.METHOD: A retrospective analysis of consecutive blood donors’ records covering the period between July 2010 and June 2013 was conducted at Dire Dawa Blood Bank, Eastern Ethiopia.RESULT: A total of 6376 blood donors were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 17 publications
(1 reference statement)
5
12
2
1
Order By: Relevance
“…4 The current study indicated that the overall seropositivity of TTIs among voluntary blood donors was 7.0%. This is in line with the reports of previous studies that were conducted in different regions of Ethiopia: 7.0% in Yirgalem, 17 7.06% in Dire Dawa, 18 6.6% in Harari, 19 and 6% in Bahir Dar. 20 On the contrary, the rate was lower than the reports of several studies conducted in Ethiopia and Africa settings like 12.4% in Eastern Ethiopia, 21 11.5% in Jigjiga, 9 12.6% in South Gondar, 22 10.1% in Zambia, 23 15.9% in Tanzania, 24 18.9% in Ghana, 25 26.2% in Cameroon, 26 and 19.3 % in Nigeria.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…4 The current study indicated that the overall seropositivity of TTIs among voluntary blood donors was 7.0%. This is in line with the reports of previous studies that were conducted in different regions of Ethiopia: 7.0% in Yirgalem, 17 7.06% in Dire Dawa, 18 6.6% in Harari, 19 and 6% in Bahir Dar. 20 On the contrary, the rate was lower than the reports of several studies conducted in Ethiopia and Africa settings like 12.4% in Eastern Ethiopia, 21 11.5% in Jigjiga, 9 12.6% in South Gondar, 22 10.1% in Zambia, 23 15.9% in Tanzania, 24 18.9% in Ghana, 25 26.2% in Cameroon, 26 and 19.3 % in Nigeria.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the sensitivity and specificity levels of the diagnostic kits might have a contribution to the variations of seropositivity rates between the studies. Studies conducted in different regions of Ethiopia revealed different seropositivity rate of HIV and HCV: 1.24% and 0.96% in Dire Dawa, 18 0.5% and 0.6% in Bahir Dar, 20 2.6% and 4.2 % in South Gondar, 22 and 1.4% and 1% in Eastern Ethiopia. 21 On the contrary, we found that none of the blood donors were positive for HIV and HCV.…”
Section: Discussionmentioning
confidence: 99%
“…Of all included studies, 36 reported HBV [ 3 , 13 , 29 62 ]; 34 reported HIV [ 3 , 13 , 29 33 , 35 38 , 42 , 43 , 45 , 46 , 48 – 58 , 60 68 ]; 31 reported HCV [ 3 , 13 , 29 33 , 35 38 , 41 43 , 45 51 , 54 , 55 , 57 , 58 , 60 62 , 69 , 70 ]; and 23 reported syphilis [ 3 , 13 , 29 – 31 , 33 , 35 , 36 , 38 , 42 , 43 , 45 , 46 , 49 52 , 54 , 57 , 58 , 60 , 68 , 71 ] prevalence among blood donors in Ethiopia. Regarding the distribution of each TTIs with sex and donor type of the study participants, it was found as follows: of 36 studies reported HBV, 24 and 9 reported sex and donor type, respectively; of 34 studies reported HIV, 24 and 8 studies reported sex and donor type, respectively; of 31 reported HCV, 19 and 7 reported sex and donor type, respectively; and of 23 studies reported syphilis, 14 and 5 studies reported sex and donor type, respectively (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the qualities of each of the included studies was evaluated using the nine items risk of bias assessment tool (Table 1). [80] 2016 Somali Blood donor Entire sampling Abera B., et al [79] 2017 Amhara HIV positive children Random sampling Abera B., et al [78] 2014 Amhara Apparently healthy Random sampling Akalu GT., et al [77] 2016 SAC Healthcare workers Convenient sampling Amsalu A., et al [76] 2018 SNNPR Pregnant women Consecutive sampling Anagaw B., et al [75] 2012 Amhara Waste handlers Unknown Asfaw MA., et al [74] 2018 SNNPR VCT Random sampling Ataro Z., et al [73] 2018 SAC Blood donors Entire sampling Ayele AG., et al [72] 2013 SAC Chronic liver diseases Convenient sampling Balew M., et al [71] 2014 Amhara HIV positive Random sampling Belayneh F., [70] 2015 SNNPR HIV positive adult Consecutive sampling Betela B., et al [87] 2018 Oromia General population Random sampling Biadgo B., et al [69] 2017 Amhara Blood donors Entire sampling Bialfew Y., et al [68] 2018 Amhara Blood donors Consecutive sampling Birku T., et al [67] 2015 Amhara Military personnel Random sampling Bisetegen FS., et al [66] 2016 SNNPR Blood donors Consecutive sampling Chernet A., et al [65] 2017 SNNPR Pregnant women Entire sampling Dabsu R., et al [64] 2014 Oromia Pregnant women Convenient sampling Demsiss W., et al [63] 2018 Amhara Students Random sampling Deressa T., et al [20] 2017 Amhara HIV positive Random sampling Deressa T., et al [62] 2018 Amhara Blood donors Entire sampling Desalegn Z., et al [84] 2013 SAC Healthcare workers Convenient sampling Desalegn Z., et al [83] 2016 Oromia Pregnant women Entire sampling Erena AN., et al [61] 2014 Oromia General population Random sampling G/micheal A., et al [60] 2013 Oromia Healthcare workers Random sampling G/egziabher D., et al [59] 2016 SAC General population Entire sampling G/mariam AA., et al [58] 2019 Amhara Healthcare professional Entire sampling Habte Y., et al [57] 2016 SAC ...…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%